Fungsi Instruktif, Konsultatif, Partisipatif dan Delegasi Dalam Melihat Fungsi Kepemimpinan Kepala Desa Kelapapati Kabupaten Bengkalis - Dedy Afrizal; Riko Saputra; Lilis Wahyuni; Erinaldi Erinaldi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2020)
The head of village must carry out its leadership function in all government of village activities. The role in planning and making decisions that are used in running the wheels of government of village. The implementation of village development planning has not been running optimally, the observation findings are still low awareness of the village apparatus and the community in carrying out orders given by the village head and the presence of apparatuses, social institutions and citizen not optimal in participating village activities. The aims of this research were to know if the leadership of the head of kelapapati village by instructive function, consultative, participatory and delegation. Using a quantitative approach by distributing questionnaires to officials of village as well as village elements involved. The findings of this study are the implementation of leadership functions of Kelapapati village is good.